Dimension of Patient Safety Culture - Purnomo, Agung; Peristiowati, Yuly; Elina, Agusta Dian (International Journal Labs, 2021)
Background: Patient safety is a serious public health issue. Several studies reported security problems in healthcare systems in various countries. The impacts were varied, starting from mild pain, disability, death, and high cost of service. Aim: This study attempted to review the culture of patient safety from several studies and to identify factors that influence them. Method: This study was conducted with systematic mapping studies related to patient safety culture. There were 10 research articles were evaluated from various online sources that related from data base ProQuest,Oxford Academic, Wiley Online Library, Google Schoolar, and Springer. It was conducted by entering keywords which appropriate to the topic, the obtained results were analyzed and discussed to produce conclusions. Findings: Adverse events were common problems. Healthcare employees had roles in creating safe and high quality services. One of them was through implementation of a culture of patient safety. There were several factors which support a culture of patient safety, namely leadership, teamwork, patient care, evidence-based, communication, learning, just, and patient-centered.